Analisis Peran Dewan Komisaris dalam Meningkatkan Tata Kelola Perseroan yang Baik: Perspektif Hukum dan Implementasinya - Achmad Nur Kholis (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This research aims to analyze the role of the Board of Commissioners in improving good corporate governance, with a focus on the legal perspective and its implementation. Good corporate governance is considered important in supporting company growth and sustainability. The method used is the normative legal research method, which is a research approach that focuses on the analysis and interpretation of existing legal norms. This research uses secondary data, such as statutory regulations, court decisions, legal theory, and the opinions of scholars as the main source of information. It is hoped that the results of this research can identify the role of the Board of Commissioners in improving good corporate governance. The legal perspective will provide an understanding of the regulatory framework that governs corporate governance, while implementation will evaluate the effectiveness of practices carried out by the Board of Commissioners. In this research, it is hoped that challenges and obstacles faced by the Board of Commissioners will be discovered in carrying out their role as well as recommendations for increasing their effectiveness. It is hoped that the results of this research can contribute to understanding the importance of the role of the Board of Commissioners in creating good corporate governance in a legal context.